2015
DOI: 10.1120/jacmp.v16i3.5427
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dosimetry Check software for IMRT patient‐specific quality assurance

Abstract: The purpose of this study is to evaluate the use of the Dosimetry Check system for patient‐specific IMRT QA. Typical QA methods measure the dose in an array dosimeter surrounded by homogenous medium for which the treatment plan has been recomputed. With the Dosimetry Check system, fluence measurements acquired on a portal dosimeter is applied to the patient's CT scans. Instead of making dose comparisons in a plane, Dosimetry Check system produces isodose lines and dose‐volume histograms based on the planning C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…6aagree well with previous publications on patient specific IMRT and VMAT QA 8,11,13,14,[35][36][37]. This might be expected from the results of the validation of the commissioning models in Section 3.B where non-transit EPID dosimetry presented higher 2L2 γ-pass rate values than transit EPID dosimetry.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…6aagree well with previous publications on patient specific IMRT and VMAT QA 8,11,13,14,[35][36][37]. This might be expected from the results of the validation of the commissioning models in Section 3.B where non-transit EPID dosimetry presented higher 2L2 γ-pass rate values than transit EPID dosimetry.…”
supporting
confidence: 89%
“…Since patient specific IMRT and VMAT QA is performed by com- IMRT and VMAT QA. 8,11,13,14,[35][36][37] Figure 6a possibly due to the same spatial resolution issues as in the case circled in blue in Fig. 6.…”
Section: Transit Epid Non-transit Epidmentioning
confidence: 82%
“…The clinical availability of DC has been investigated by various research groups for DQA of linear accelerator (LINAC) and TomoTherapy ® ‐based IMRT plans . These studies reported that the DC‐calculated 3D volumetric gamma pass rates for the patient‐specific DQAs were greater than 90%.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible to have discrepancies between the TomoTherapy ® TPS and DC‐calculated DVHs for target or normal structures even though the 3D volumetric gamma pass rates for the corresponding structures satisfy the gamma pass criteria. Especially when the tissue inhomogeneity is present in the target or surrounding normal structures, the dose distribution difference can be present due to the inherent difference of the dose calculation algorithm between the CCC algorithm in DC and convolution/superposition algorithm in TomoTherapy ® TPS . Users may need to determine the acceptable limit of the discrepancy about the DVH between the TomoTherapy ® TPS and DC.…”
Section: Discussionmentioning
confidence: 99%
“…All plans had been recalculated in the Tomotherapy phantom (Cheese phantom) and delivered with the couch out of the bore. Dosimetry Check software v.5.5 (LifeLine Software Inc., Austin, TX, USA) was used to reconstruct the measured dose distribution from the acquired sinogram 17,18 . Three-dimensional global gamma analysis was performed with 3% of maximum dose/3 mm distance-to-agreement criteria and 10% dose threshold (TH) for head and neck and prostate, and 3%/2 mm 10% TH for stereotactic brain plans.…”
Section: A | Treatment Plans and Deliverability Evaluationmentioning
confidence: 99%